2012
DOI: 10.1007/s12032-012-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum C-reactive protein level predicts poor prognosis in patients with hepatocellular carcinoma

Abstract: C-reactive protein (CRP) is known to be associated with poor prognosis in patients with various malignancies. We investigated the relationship between the pretreatment serum CRP level and survival in patients with hepatocellular carcinoma (HCC) in various stages of the disease. A cohort of 133 patients with newly diagnosed HCC was prospectively evaluated. The patients were divided into two groups: high-CRP group (n=27) with the pretreatment serum CRP level≧1.0 mg/dl and low-CRP group (n=106) with the CRP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 27 publications
1
54
0
2
Order By: Relevance
“…Serum CRP, an acute-phase protein, is produced in hepatocytes, predominantly under the control of interleukin-6, and is a very sensitive prognostic indicator of inflammation in various cancers (21,22). Based on our current observations, it is suggested that CAR, which is calculated from both serum CRP concentrations and albumin levels, may better predict cancer outcome.…”
Section: Discussionmentioning
confidence: 77%
“…Serum CRP, an acute-phase protein, is produced in hepatocytes, predominantly under the control of interleukin-6, and is a very sensitive prognostic indicator of inflammation in various cancers (21,22). Based on our current observations, it is suggested that CAR, which is calculated from both serum CRP concentrations and albumin levels, may better predict cancer outcome.…”
Section: Discussionmentioning
confidence: 77%
“…In conclusion, our data suggest that long-term suppression of TRAIL expression and release by CRP might contribute to increase the risk of tumors associated to chronic diseases, which are characterized by systemic inflammation and CRP elevation (55)(56)(57). However, only in vivo experiments carried out by simultaneously analyzing the levels of CRP and TRAIL in patients with premalignant lesions or overt cancer will reveal whether our in vitro data have clinical relevance.…”
Section: Primary Cd14mentioning
confidence: 86%
“…In assessing crp elevation, the presence of other inflammatory disease should be considered, because crp is a nonspecific inflammatory marker [15][16][17] . However, measurements of serum crp are simple and low-cost.…”
Section: Discussionmentioning
confidence: 99%